Methods for the Preparation of Blood Serum Samples in the Assessment of the Pharmacokinetics of Protein Drugs by the Example of Viscumin - Yudina, N.S.; Barashkova, Ya.N.; Vladimirova, O.V.; Myasnikov, V.A. (Biomedical Chemistry: Research and Methods, 2021)
A comparative evaluation of methods for preparing blood serum samples for determination of the lectin content of the mistletoe Viscum Album, viscumin, by high-performance liquid chromatography in combination with high-resolution mass-spectrometry detection has been carried out. Based on the results of the analysis of the lectin hydrolyzate, a specific peptide fragment with m/z 791.388 suitable for subsequent quantitative determination was selected. Isolation of viscumin from serum components was carried out without the use of specific antibodies. The study used methods employing various spin columns and the method of protein precipitation with 1% TCA (trichloroacetic acid) in IPA (isopropyl alcohol). Testing the methods of depletion of blood serum proteins was based on the determination of the degree of extraction of lectin from model serum samples. As a result of our research, we have developed a technique for the quantitative analysis of viscumin in blood serum by the most efficient method of sample preparation using the ProteoMiner spin columns. The technique allows to determine the protein concentration up to 5·10-4 mg/ml with the extraction degree (2.7 ± 0.6) %.